Effects of Caragana korshinskii aqueous extract on growth performance, antioxidant capacity, and immune function of sheep under cold stimulation - B. Pan; J. Yang; J. Li; M. Xu; M. Yang; M. Yang; M. Peng; J. Cheng; S. Xue; J. Wang (Archives Animal Breeding)
Cold stimulation can impair the immune and antioxidant functions of animals, which further leads to a decline in animal production performance. This study aimed to investigate the effect of the aqueous extract of Caragana korshinskii (CK) on the antioxidant and immunological properties of sheep under oxidative stress induced by cold stimulation. In this study, a total of 54 healthy 2-month-old sheep were randomly divided into six groups, namely the control group and experimental groups I–V. The control group sheep were fed the basal diets, while the sheep in experimental groups I–V had their diets supplemented with 4, 6, 8, 10, and 12 g kg−1 of CK aqueous extract, respectively; the sheep from all groups were housed in semi-closed enclosures for 65 d (the pre-trial period was 15 d, and the experimental period was 50 d) in a cold environment (−20 to −10 °C). The results showed that the final body weight and average daily gain (ADG) of sheep in groups I, II, and III were significantly increased compared with the control group (p<0.05), but there was no significant difference in average daily feed intake (ADFI) (p>0.05). Total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-Px), and superoxide dismutase (SOD) were decreased (p<0.05); malondialdehyde (MDA) was increased (p<0.05); and the tumour necrosis factor-α (TNF-α), interleukin-2 (IL-2), and interleukin-6 (IL-6) were increased (p<0.05), whereas interleukin-10 (IL-10), immunoglobulin G (IgG), and immunoglobulin M (IgM) were decreased (p<0.05) in the blood of the control sheep after 50 d of cold stimulation. In contrast, T-AOC, GSH-Px, and SOD increased (p<0.05); MDA decreased (p<0.05); and TNF-α, IL-2, and IL-6 decreased (p<0.05), whereas IL-10, IgM, and IgG increased (p<0.05) in the group with the addition of CK aqueous extract. Moreover, the CK aqueous extract decreased MDA (p<0.05) and increased T-AOC, GSH-Px, and SOD in sheep liver (p<0.05) and decreased TNF-α, IL-2, and IL-6 (p<0.05) and increased IL-10, IgM, and IgG in the thymus and spleen (p<0.05). These results suggest that the addition of CK aqueous extract can promote sheep growth and improve oxidative stress, inflammation, and immune response to chronic cold stimulation in sheep.